Corporate governance: a review of specialized literature - Jara Pinilla, Natalia; Jara Bertin, Mauricio Alejandro (Estudios de Administración, 2014)
The governance of the company has been a topic that has gained increasing importance in the corporate world. Although its beginnings in terms of formal discussion date back to the mid-70,the underlying concept has its roots long back in time. The problem originates from the agency theory, which exposes a conflict of interest between shareholders and suppliers. There are several definitions of Corporate Governance, all pointing to a system of internal and external mechanisms that mitigate the agency problem among the different participants of the large modern company. Among some factors that can shape the significance of relationships within the company are legal systems, which give rise to the relative importance of both external mechanisms, as the market, and internal mechanisms such as the board of directors.